Pengembangan Media Digital Papan Pintar Mata Pelajaran PAI Untuk Kelas 3 Sekolah Dasar - Yudi Hadiansyah; N.Fitri Amaliya; Zaky, Abdullah (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
Based on the results of a survey conducted at Pamanukan Elementary School, Subang City, it is known that not all classes apply digital media in the classroom. The aim of this research is to create smart products from media products and to improve the effectiveness and quality of PAI learning for basic education students. This research uses the reach and development method with research setting in basic education. These media are divided into 5 categories. The first category is analysis, the second category is design, the third category is development, the fourth category is implementation, and the fifth category is evaluation.